DILALAH MANTHUQ AND MAFHUM IN THE IMAM SYAFI'I PERSPECTIVE - Ahmad Fadli Fauzi (Universitas Islam Negeri (UIN) Mataram, 2019)
If traced the meaning contained in each verse of the Qur’an , it turns out that many verses still need a deeper explanation of the law contained in the verse. This means that the verses of the Qur’an not only provide a direct and clear understanding, but there are verses of the Qur’an whose meaning is implied in them. The lafaz instructions for meaning are sometimes based on the sound (manthuq) of the spoken word, both explicitly and possibly containing other meanings in it. And sometimes based on understanding (mafhum) both the law in accordance with the law manthuq or contradictory. This is what is called Manthuq and Mafhum.